Purification System of Domestic Waste Incineration Flue Gas. Issue 3 (May 2020) - Pan, Wenbo; Zhong, Shaotao; Geng, Man; Chen, Dingsheng
Abstract: Flue gas will be emitted during the waste incineration power generation process. The flue gas contains toxic and harmful ingredients. If it is not treated, it will cause serious harm to human health and the environment. Therefore, the incineration flue gas needs to be purified. In this paper, combined with the monitoring of a large-scale waste incineration power plant incinerator flue gas purification treatment project, the combined process of "in-furnace denitrification (SNCR) + semi-dry deacidification + slaked lime and activated carbon (dry process) injection + bag filter". The purification effect of flue gas shows that the process has a good purification effect on domestic waste incineration flue gas. This study can provide reference and basis for the treatment of incineration flue gas in the industry.